Role of Stakeholder in Implementation of Conservation Function in Ir. H. Djuanda Forest Park - Fandawa Saputra; Tutut Sunarminto; Harnios Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Tahura as a conservation area has many benefits, functions, and impacts. This creates many interests and influences from various parties to Tahura Djuanda, so that the management of conservation in Tahura Djuanda needs to be managed together. Co-management is urgently needed to know each other's roles. Therefore, it is important to know the role of Tahura Djuanda Stakeholder in the implementation of conservation functions. The purpose of this study identifies the role of Stakeholder in the implementation of conservation functions and linkages among Stakeholder. This research was conducted in Tahura Djuanda and the location of Stakeholder existence, with the subject of research are Stakeholder and research object that is Tahura Djuanda. Data collection methods used were questionnaires, interviews, observation, and literature study. Tahura Djuanda's Stakeholder are 24 and grouped in government agencies, private institutions and community institutions. The role of Stakeholder in the aspects of protection, preservation, and utilization tends to be good with the interrelationship between Stakeholder that are mutually beneficial. Keywords: conservation, roles, Stakeholder, Tahura Djuanda